In situ transesterification of solid coconut waste in a packed bed reactor with CaO/PVA catalyst - Talha, Nur Syakirah; Sulaiman, Sarina (Elsevier, 2018)
In this study, solid coconut waste and CaO/PVA was used as raw material and catalyst respectively to produce biodiesel through in situ transesterification. Both, raw material and catalyst were packed in a packed bed reactor. The reaction was fixed for 3 h and the mixing was kept constant at 350 rpm. The highest biodiesel yield of 95% was obtained at reaction temperature of 61 °C with catalyst loading (CaO/PVA) of 2.29 wt% and methanol to solid ratio of 12:1. CaO-waste derived catalyst has been successfully proven to be utilized as heterogeneous base catalyst for the production of biodiesel from solid coconut waste.